We can have the cake and eat it too: leisure and spirituality at 'veiled' hotels in Turkey. Issue 2 (3rd March 2016) - Sehlikoglu, Sertaç; Karakas, Fahri
Abstract : This paper uses ethnographic methods to inquire how new forms of consumption arise as a result of bridging Islamic spirituality with leisure in the newly growing tesettür hotels in Turkey, which have become a magnet of popular and academic attention. We aim to offer a multi-layered analysis of the leisure and consumption practices of Muslim women in the context of the new Islamic hospitality industry by looking at the interactions between spiritual Islam and modern capitalism. We focus on the consumption process of the female customers of these hotels as part of defining and redefining their newly developing identity that is Islamic and spiritual; as well as modern and luxurious. The study responds to the call of Gökarıksel and Secor to analyse new Islamic patterns of consumption and leisure by building on their perspectives bridging neoliberal capitalism and resurgence of Islamic identities. We call for a critical and contextual perspective to understand the dynamic emergence of new forms of Islamic lifestyles and capitalism; emphasising a future agenda of further research that is sensitive to the complexities of desires and leisure activities of veiled Muslim women in diverse countries.